Banana genotype-associated microbiomes play an essential role in suppressing Fusarium wilt - Zhang, Wenlong; Xu, Shengtao; Bai, Tingting; Aman, Bonaventure Omondi; Wang, Yongfen; Li, Shu; Wang, Jielin; Qin, Yue; Wang, Yun-Yue; Zheng, Sijun (BioMed Central, 2025)
Introduction: Fusarium wilt of banana (FWB) seriously threatens the banana industry’s sustainable development. Recent evidence indicates that FWB occurrence and development are not only regulated by host resistance genes, but are also significantly influenced by host microbiomes. However, the link between banana genotypes and genotype-associated microbiomes remains unclear.